qual a derivada de y= 1-x/x+3
Soluções para a tarefa
Respondido por
1
Usando a regra do quociente, temos:
y' =
![\frac{ - 1(x + 3) - (1 - x) \times 1}{ {(x + 3)}^{2} } = \frac{ - x - 3 - 1 + x}{ {x}^{2} + 6x + 9 } = \\ = \frac{ - 4}{ {x}^{2} + 6x + 9} \frac{ - 1(x + 3) - (1 - x) \times 1}{ {(x + 3)}^{2} } = \frac{ - x - 3 - 1 + x}{ {x}^{2} + 6x + 9 } = \\ = \frac{ - 4}{ {x}^{2} + 6x + 9}](https://tex.z-dn.net/?f=+%5Cfrac%7B+-+1%28x+%2B+3%29+-+%281+-+x%29+%5Ctimes+1%7D%7B+%7B%28x+%2B+3%29%7D%5E%7B2%7D+%7D++%3D++%5Cfrac%7B+-+x+-+3+-+1+%2B+x%7D%7B+%7Bx%7D%5E%7B2%7D+%2B+6x+%2B+9+%7D++%3D++%5C%5C++%3D++%5Cfrac%7B+-+4%7D%7B+%7Bx%7D%5E%7B2%7D++%2B+6x+%2B+9%7D+)
y' =
sarahsouza2010:
obrigada gênio ^^
Perguntas interessantes
Matemática,
11 meses atrás
História,
11 meses atrás
Geografia,
11 meses atrás
Artes,
1 ano atrás
Matemática,
1 ano atrás